IMPERATIVE SEMANTICS AND ITS FEATURES IN THE ENGLISH AND UZBEK LANGUAGES - Kenjayeva, Lobar (INTERNATIONAL CONFERENCES, 2023)
This article deals with the semantic features of imperative statements in English and Uzbek languages. Also article emphasizes that the function of prompting to action is one of the oldest functions of the language. The language has various means of expressing this function. It is noted that the role of imperative statements in the language as a means of communication between people is exceptionally great. Their main function is to express a direct will, and they have specific grammatical features. Unlike declarative sentences, imperative sentences do not contain a message about some fact of objective reality, but an inducement of the addressee to a certain action.